Innovative Grouting Reinforcement Techniques for Shield Tunnels: A Case Study on Surface Settlement Mitigation - Qiang Ma; Xingchi Zhang; Hang Shu (Applied Sciences)
This study investigates the impact of flower tube grouting reinforcement on surface settlement in shield tunnels under complex geological conditions, using the Wuhan Metro Line 12 project as a case example. A simulation model was constructed using PLAXIS 3D software to analyze surface settlement under unreinforced conditions and compare it with reinforced conditions. The effects of grouting pressure, soil pressure, and tunnel depth on surface settlement were also examined. Results indicate that surface settlement decreases with increasing tunnel depth, decreasing by approximately 0.15 mm per 1 m increase in depth. Soil silo pressure positively correlates with surface settlement, increasing by about 0.08 mm for every 10 kPa rise in pressure. A critical grouting pressure of approximately 400 kPa was identified, beyond which surface settlement increases with higher grouting pressure. Flower tube grouting significantly reduced surface settlement, by 92% on average, limiting maximum settlement to 3 mm. Numerical simulation results closely matched field monitoring data, with errors within ±0.5 mm, validating the model’s reliability. The study demonstrates that flower tube grouting reinforcement effectively mitigates the effects of tunnel depth, grouting pressure, and soil bin pressure on surface settlement, ensuring project safety when shield tunnels pass through sensitive areas such as long-distance railroads.